Komodifikasi Empati: Eksplorasi Fenomena ‘Ngemis dan Nyawer’ Online di Media Sosial TikTok - Cakrawala, Jatayu Bias; Permatasari, Alfia Rahma; Khoirunnisa, Wahida Okta; Elsyifa, Avisena Kemal; Purwaningtyas, Mashita Phitaloka Fandia (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
The development of social media has created an opportunity for the perpetuation of poverty exploitation in which is mediated through social platforms, for instance, aid that was once given directly is now conveyed through digital features, as seen in one of TikTok’s functionalities, thus giving rise to the emergence of a novel form of commodification, known as “empathy commodification”. This research aims to examine the process of empathy commodification and understand the public’s responses to the phenomenon of online “ngemis dan nyawer” on the TikTok social media platform. Subsequently, strategies will be formulated to mitigate poverty exploitation in the media. The research employs a mixed-method approach with sociocultural approach and interpretative paradigm. Data is collected through content analysis, surveys, in-depth interviews, and literature studies. The research findings indicate that the process of empathy commodification on TikTok occurs through the live streaming feature, with audience empathy being commodified through economic-value gifts. Strategies to reduce poverty exploitation in the media can be achieved by social media campaigns